Efficacy and safety of lacosamide as an adjunctive therapy for refractory focal epilepsy in paediatric patients: a retrospective single‐centre study. Issue 4 (25th January 2016) - Toupin, Jean‐François; Lortie, Anne; Major, Philippe; Diadori, Paola; Vanasse, Michel; Rossignol, Elsa; D'Anjou, Guy; Perreault, Sebastien; Larbrisseau, Albert; Carmant, Lionel; Birca, Ala
Abstract: Aim . Lacosamide is an antiepileptic drug approved for the treatment of focal epilepsy in adult patients. The aim of this observational study was to review our centre's experience with lacosamide and to characterize its effectiveness and tolerability as an adjunctive antiepileptic drug in a retrospective cohort of children with refractory focal epilepsy. Methods . We retrospectively reviewed the medical records of 22 patients who received lacosamide from November 2009 to April 2014 at the CHU Ste‐Justine, University of Montreal. Treatment responders were defined as children with a ≥50% reduction in seizure frequency compared to baseline, and this was determined three months after the initiation of treatment and at the last follow‐up visit. Results . We included 14 boys and eight girls with a mean age of 12.9 years (SD: 5.2; range: 5.2–20.7 years) at the initiation of treatment. The average length of follow‐up was 11.9 months. Patients had previously received an average of 7.5 antiepileptic drugs. The mean number of concomitant antiepileptic drugs was 2.3. The mean initial and maintenance doses were 2.9 and 8.4 mg/kg/d, respectively. Thirteen (59%) and ten (45%) patients were responders after three months of treatment and at the last follow‐up visit, respectively. One became seizure‐free. Adverse effects were reported in 11 patients and none were severe. Responders and non‐responders were identical with respect to all studied parameters except gender, with the proportion of responders being greater in girls than in boys (75% vs 29%; p =0.035). Conclusion . Our study adds evidence that lacosamide appears to be a safe and effective adjunctive therapy for children with refractory focal epilepsy.